2001
DOI: 10.1002/tcm.1035
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of chemotherapy‐induced DNA damage in peripheral blood leukocytes of cancer patients using the alkaline comet assay

Abstract: The alkaline comet assay was employed to assess the pre-and post-treatment levels of in vivo DNA damage in peripheral blood leukocytes of cancer patients. During the study all patients were given antineoplastic drugs, mainly as polychemotherapy. To quantify the DNA damage, two different comet parameters were evaluated: the tail length and the tail moment. Our results indicate marked interindividual variations between baseline DNA damage in peripheral blood leukocytes recorded among cancer patients prior to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
0
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 52 publications
6
20
0
7
Order By: Relevance
“…4 In addition, the difference between the amount of drug needed to induce successful tumoricidal action and the amount needed to induce toxicity in the host is small and depends on individual characteristics. 8 Because radiation and most of the drugs applied in breast cancer treatment affect DNA, DNA damage must be considered as a plausible therapy side effect. 15 It has been reported that the comet assay, using peripheral blood lymphocytes, is sensitive enough to detect DNA damage as a result of the cancer treatments because lymphocytes are also affected by the treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 In addition, the difference between the amount of drug needed to induce successful tumoricidal action and the amount needed to induce toxicity in the host is small and depends on individual characteristics. 8 Because radiation and most of the drugs applied in breast cancer treatment affect DNA, DNA damage must be considered as a plausible therapy side effect. 15 It has been reported that the comet assay, using peripheral blood lymphocytes, is sensitive enough to detect DNA damage as a result of the cancer treatments because lymphocytes are also affected by the treatments.…”
Section: Discussionmentioning
confidence: 99%
“…7 DNA damage caused by anti-neoplastic drugs and ionizing radiation includes nucleotide damage, breaking of hydrogen bonds between the two helices, single-strand breaks, double-strand breaks, appearance of apurinic or apyrimidinic sites, DNA protein cross-links, DNA-DNA interstrand crosslinks, DNA intrastrand cross-links, and generation of reactive oxygen species, which, in turn, cause more DNA damage. 2,8,9 DNA damage related to the exposure of cancer patients to therapy is frequently determined using peripheral blood lymphocytes as target cells. Lymphocytes have been proven to be good surrogate cells with which to investigate DNA damage because they are affected by agents used in cancer treatment and also are easy to obtain.…”
Section: A U T H O R P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…A key challenge in RT is to maximize radiation doses to cancer cells while minimizing damage to the surrounding non-target healthy tissue. Recent literature in the field of clinical oncology and RT still does not explain sufficiently the question of damages to non-target cells and tissues after chemo-radiation treatment [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Jelentősége a sejtminták csökkentett számának a követelményén alapszik, képes számokban kifejezni a DNS-károsodást a nem proliferáló sejtekben [2,3].…”
unclassified